Integral of cos^3xsin^2xdx dx
The solution
Detail solution
-
Rewrite the integrand:
cos3(x)sin2(x)1=(1−sin2(x))sin2(x)cos(x)
-
There are multiple ways to do this integral.
Method #1
-
Let u=sin(x).
Then let du=cos(x)dx and substitute du:
∫(−u4+u2)du
-
Integrate term-by-term:
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−u4)du=−∫u4du
-
The integral of un is n+1un+1 when n=−1:
∫u4du=5u5
So, the result is: −5u5
-
The integral of un is n+1un+1 when n=−1:
∫u2du=3u3
The result is: −5u5+3u3
Now substitute u back in:
−5sin5(x)+3sin3(x)
Method #2
-
Rewrite the integrand:
(1−sin2(x))sin2(x)cos(x)=−sin4(x)cos(x)+sin2(x)cos(x)
-
Integrate term-by-term:
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−sin4(x)cos(x))dx=−∫sin4(x)cos(x)dx
-
Let u=sin(x).
Then let du=cos(x)dx and substitute du:
∫u4du
-
The integral of un is n+1un+1 when n=−1:
∫u4du=5u5
Now substitute u back in:
5sin5(x)
So, the result is: −5sin5(x)
-
Let u=sin(x).
Then let du=cos(x)dx and substitute du:
∫u2du
-
The integral of un is n+1un+1 when n=−1:
∫u2du=3u3
Now substitute u back in:
3sin3(x)
The result is: −5sin5(x)+3sin3(x)
Method #3
-
Rewrite the integrand:
(1−sin2(x))sin2(x)cos(x)=−sin4(x)cos(x)+sin2(x)cos(x)
-
Integrate term-by-term:
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−sin4(x)cos(x))dx=−∫sin4(x)cos(x)dx
-
Let u=sin(x).
Then let du=cos(x)dx and substitute du:
∫u4du
-
The integral of un is n+1un+1 when n=−1:
∫u4du=5u5
Now substitute u back in:
5sin5(x)
So, the result is: −5sin5(x)
-
Let u=sin(x).
Then let du=cos(x)dx and substitute du:
∫u2du
-
The integral of un is n+1un+1 when n=−1:
∫u2du=3u3
Now substitute u back in:
3sin3(x)
The result is: −5sin5(x)+3sin3(x)
-
Add the constant of integration:
−5sin5(x)+3sin3(x)+constant
The answer is:
−5sin5(x)+3sin3(x)+constant
The answer (Indefinite)
[src]
/
| 5 3
| 3 2 sin (x) sin (x)
| cos (x)*sin (x)*1 dx = C - ------- + -------
| 5 3
/
−153sin5x−5sin3x
5/p\ 3/p\
sin |-| sin |-|
\2/ \2/
- ------- + -------
5 3
−5sin5(2p)+3sin3(2p)
=
5/p\ 3/p\
sin |-| sin |-|
\2/ \2/
- ------- + -------
5 3
−5sin5(2p)+3sin3(2p)
Use the examples entering the upper and lower limits of integration.